(untitled) (JURNAL ADMINISTRASI PUBLIK, 2020)
The purpose of this study is to find out and describe how the supervision of the education department in the management of school operational assistance funds in Pinolosian Subdistrict, Bolaang Mongondow Selatan District. The research method used in this research is descriptive research method with a qualitative approach. Data collection in this study was carried out through interviews, observations and document collection. While the data analysis techniques that researchers use are qualitative with the Lexy J. Moleong descriptive approach. Based on research results Problems that arise in the management of BOS funds are weak oversight of related agencies in this case the Office of Education. Providing School Operational Assistance funds that are not on target is wasting money because it can lead to misappropriation, to prevent this, involving the community must oversee the implementation and distribution of BOS.a conclusion can be drawn that the function of monitoring BOS funds by the Education Office and the Management Team of South Bolaang Mongondow Regency is carried out well only it needs to be maximized. There are a number of deviations done by the schools in the form of a discrepancy in the accountability report with the reality in the field and there are some schools that do not follow the technical guidelines in the form of no information boards on the use and management of BOS funds in schools. Errors or deviations in the implementation or use of BOS funds at schools, the District Management Team gives a warning and carries out / corrects or corrects. Keywords : measure, compare, correction / corrective actions